Study on Maternal and Immediate Fetal outcome of placenta previa - Lama, Sushma; Ranjit, S (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: This study aimed to analyze the demographic profile, maternal and fetal outcome of placenta previa. Methods: This was a retrospective study done at Patan Academy of Health Sciences. The study population comprised of all the patients that had caesarean section for placenta previa from April 2012 to October 2015. All patients diagnosed with placenta previa clinically, ultrasonograph or incidentally during caesarean sections were recruited in this study. The data were obtained from medical records and hospital database system. Individual charts were reviewed and data on various parameters were collected. Results: In Patan hospital, there were total 126 placenta previa cases out of 21,552 deliveries during the two and half year period hence the incidence was 0.58 %. We were able to retrieve patient records of only 108 of 126 cases. The incidence of placenta previa was higher with increasing maternal age ≥30 years (41.67%), more common in multigravida (65.74%). We found that associated risks factors included previous CS, multiparity and dilatation and curettage (40.74%). Eleven patients required blood transfusion, seven of them had blood loss of 1000-1400 ml, one had blood loss of 2000 ml. Also, Caesarean hysterectomy were performed in two patients. In term of fetal outcomes, 37.04% were preterm birth and 29.63% of the babies had low birth weight. There was one incident of congenital anomaly, one intrauterine fetal death and six neonatal deaths. Conclusions: Placenta previa is an obstetrics complication that is potentially life threatening to both the mother and the baby.